Endobronchial management of malignant central airway obstruction: the first 6-year single center experience - Aktaş, Zafer; Yılmaz, Aydın; Öztürk, Ayperi; Güllü, Yusuf Taha; Karataş, Mevlüt (The European Research Journal, 2019)
Objectives: Central airway obstruction (CAO) develops in 20-30% of lung malignancies during the disease. The symptoms related to obstruction often result in poor quality of life and poor prognosis. Interventional bronchoscopic treatments are now recommended in guidelines to improve quality of life and symptom palliation in this patient group. In our study, we aimed to determine the efficacy and safety of our methods in the malignant CAO caused by endobronchial exophytic tumors. Methods: Between May 2012 and August 2018, 432 endobronchial debulking procedures were performed in 388 patients with symptomatic malignant CAO due to endobronchial exophytic or mixed lesions. Results: Primary lung tumors were the most common cause of airway stenosis (84.0%). The most common debulking technique was argon plasma coagulation assisted mechanical debridement (APC+MD) (79.9%). Airway patency was achieved with additional stents (10.2%) in the operations. The success rate of airway patency was 85.5% in APC+MD method, 75.6% in cryorecanalisation method, 91.7% in electrocautery assisted MD method, 100% in MD method and overall success rate was 85.4%. Stent use rate was significantly higher in the stenosis around main carina (42.9%) than in other localizations (p < 0.001). The overall serious complication rate was 2.1%. Procedure-related dead rate was 0.2%. Conclusions: Endobronchial treatment of malignant CAO with interventional bronchoscopic procedures is effective and safe. The first 6 years of experience in our interventional pulmonary clinic show that it has similar characteristics with the world experience in the endobronchial treatment of malignant CAO.